Misconceptions, not evidence guide occupational physicians' decisions on legionellosis prevention. (13th November 2019) - Riccò, M; Balzarini, F; Mezzoiuso, A G; Colucci, M E; Catellani, W; Veronesi, L; Corradi, M
Abstract: Introduction: Legionnaire's diseases (LD) is a significant cause of community-acquired pneumonia. An increasing number of cases has been linked with occupational exposures. The aim of this study was understanding knowledge, attitudes and practices of occupational physicians (OPh) towards LD. Methods: A questionnaire-based cross-sectional study (April 2019), collecting a convenience sample of OPh operating in the Parma Province. Knowledge status (KS), Risk Perception (RP), and actual participation to the LD risk assessment were assessed. Multivariate odds ratios (mOR) for factors associated with participation to the LD risk assessment were calculated by means of a binary logistic regression analysis. Results: 80 OPh participated to the survey (76.9% participation rate; mean age 48.2±11.2 years): even though the majority of them assisted at least one enterprise at potentially high risk for LD (i.e. 41.4% retirement houses, 27.1% water treatment plants including spas and pools, 25.7% hospitals) only 42.9% had participated to the LD risk assessment. The majority of OPh did not acknowledge diabetes (52.9%), cancer (65.7%), alcoholism (77.1%) as risk factors for LD, while a large share of OPh did not recognize hospital (50.0%), retirement houses (48.6%), swimming pools (48.6%) and spas (35.7%) as high risk environments. Moreover, participants underestimated both actual frequency (>1000 cases/year) and severity (lethality 10-15%) of LD in Italy, and occupational RP was not coincidentally low (43.2%±20.3). Participants reporting better KS were more likely to participate to the risk assessment (mOR 4.82 95%CI 1.06-21.94), while RP was eventually unrelated with preventive practices. Conclusions: OPhs were diffusely affected by significant knowledge gaps on the actual risk factors for LD. Their misperceptions have the potential to negatively influence daily practice, impairing prevention of LD on the workplaces, and should be specifically targeted by information campaigns. Key messages: Occupational Physicians were affected by significant knowledge gaps, particularly on individual and occupational risk factors for legionnaire disease. In order to better address the increasing threat of Legionnaire Disease, Occupational Physicians should be specifically targeted by information campaings.